2016
DOI: 10.1177/0037549716678659
|View full text |Cite
|
Sign up to set email alerts
|

A utility threshold model of herding–panic behavior in evacuation under emergencies based on complex network theory

Abstract: Casualties during crowd evacuation in many unexpected events are closely related to panic behaviors. In this paper the evacuation crowd system is abstracted into a dynamic complex network composed of three types of people, namely calm people, panic people, and herding people, as well as their interactions. The mathematical model of these interactions is established based on complex network theory. Further, the evolution of herding people to panic people is interpreted by a specific concept of ''herding-panic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The findings of other studies about the effect of the passengers' behavior on the efficiency of emergency evacuation of subway stations also have shown that the spread of panic among passengers could cause secondary incidents, which was consistent with our findings . [8][9][10]29 According to the findings of the propagation model of panic in the subway emergency in Shanghai, China, hurrying to exit and escape has led to herding behavior of the populations and stampede, which caused the people to be trampled underfoot especially the disabled ones, dispersing the luggage, and seriously dis- turbing social order and public transportation. 11 According to the findings of other studies, one reason for such behavior is that one of the phenomena of collective behavior in emergencies is following a fleeing crowd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of other studies about the effect of the passengers' behavior on the efficiency of emergency evacuation of subway stations also have shown that the spread of panic among passengers could cause secondary incidents, which was consistent with our findings . [8][9][10]29 According to the findings of the propagation model of panic in the subway emergency in Shanghai, China, hurrying to exit and escape has led to herding behavior of the populations and stampede, which caused the people to be trampled underfoot especially the disabled ones, dispersing the luggage, and seriously dis- turbing social order and public transportation. 11 According to the findings of other studies, one reason for such behavior is that one of the phenomena of collective behavior in emergencies is following a fleeing crowd.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] On the other hand, the panic among the population caused by such incidents, precipitates secondary incidents increasing the destructive impact of the whole incidents. [8][9][10] For instance, the sudden braking and stopping of the Guangzhou Subway in 2013 caused the passengers of the last wagon to flee to the front of the wagon with terror leading to a number of injuries due to the stampede of the population. 11 Iran is a middle-income country, where subway has been constructed and utilized in eight metropolises including the capital city of Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…The emergency evacuation during an urban rainstorm involves the interaction and decision-making of a large number of pedestrians. It is a complex, adaptive system [43]. The key issue to obtain the pedestrians' evacuation route in urban waterlogging is how to set the experimental process.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…For the current state of the ship agent, the decision-making unit will search for the corresponding decision tree, and the search result may have multiple results. Among them, the decision that satisfies the conditions of each node is selected as the final decision and submitted to the execution module [41].…”
Section: ) the Decision Modulementioning
confidence: 99%